Symposium 1: Facilitating Adoption of Web Tools for Problem and Project Based Learning Activities - Khalid, Md. Saifuddin; Rongbutsri, Nikorn; Buus, Lillian (Proceedings of the International Conference on Networked Learning, 2012)
This paper builds on research directions from ‘activity theory’ and ‘learning design’ to provide ‘facilitation’ for students standing within decision making related to selection of web 2.0 tools and university provided web-based applications for supporting students activities within problem and project based learning. In the area of problem and project based learning, facilitation is the core term and the teacher often has the role as facilitator or moderator instead of a teacher teaching. Technology adoption for learning activities needs facilitation, which is mostly absent. Sustainable adoption might be facilitated based on tool appropriation with activities associated with courses and projects. Our mapping of different tools in a framework is reported based on interviews, observations, narratives and survey. A direction towards facilitation process for adoption is discussed as part of future scope of work.